2017
DOI: 10.1093/toxsci/kfx047
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Has Dose-Dependent Toxicity on Mouse Ovarian Follicle Development, Hormone Secretion, and Oocyte Maturation

Abstract: Doxorubicin (DOX), one of the most commonly used anticancer medications, has been reported to affect fertility by damaging ovarian follicles; however, the dose-dependent toxicity of DOX on the dynamic follicle development and oocyte maturation has not been well-defined. Our objective is to determine the effects of human-relevant exposure levels of DOX on follicular functions across developmental time. In vitro cultured multilayered secondary mouse follicles were treated with DOX at 0, 2, 20, 100, and 200 nM fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
29
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 46 publications
4
29
1
6
Order By: Relevance
“…A previous study has demonstrated that chemotherapy induced follicle apoptosis, resulting in impaired ovarian function, and even sterility [43]. For instance, the chemotherapeutic agent doxorubicin induces follicular apoptosis, affects follicular development, hormone secretion, oocyte maturation, and shortens the fertility window [27,44,45]. Therefore, to determine whether epirubicin, an isomer of doxorubicin, behaves similar to doxorubicin in the ovary is of great significance due to its popular application in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has demonstrated that chemotherapy induced follicle apoptosis, resulting in impaired ovarian function, and even sterility [43]. For instance, the chemotherapeutic agent doxorubicin induces follicular apoptosis, affects follicular development, hormone secretion, oocyte maturation, and shortens the fertility window [27,44,45]. Therefore, to determine whether epirubicin, an isomer of doxorubicin, behaves similar to doxorubicin in the ovary is of great significance due to its popular application in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…При изучении общей токсичности лекарственных веществ и некоторых видов специфической токсичности (например, репродуктивная токсичность), следует определять уровень СТГ, поскольку гормон не только ответствен за рост костей, развитие органов, метаболизм и энергетический гомеостаз, но и является одним из факторов регуляции полового созревания и фертильности у мужчин и женщин. Например, несмотря на то что есть данные о прямом токсическом действии препарата Доксорубицин на фолликулы яичника, опосредованном влиянии на секрецию гормона эстрадиола и созревание ооцитов [7], эффект может быть обусловлен также действием препарата на СТГ. Однако работ, которые бы напрямую оценивали влияние препарата на уровень СТГ, не найдено.…”
Section: заключениеunclassified
“…В соответствии с руководствами анализ состояния эндокринного статуса не является обязательным и проводится в случае, если известны свойства тестируемого образца в отношении эндокринной системы. Некоторые ЛП (например, доксорубицин, салиномицин) оказывают негативное влияние на репродуктивную систему, развитие фолликулов, сперматогенез, и это действие может быть опосредовано, в том числе влиянием на эндокринную систему [6,7]. Однако такую информацию с описанием возможных рисков можно найти не для всех новых соединений или она отсутствует, тогда ответственность при оценке уровня гормонов берет на себя исследователь.…”
Section: Introductionunclassified
“…[5]. Doxorubicin can cause ovarian toxicity [6][7][8], including impaired ovarian hormone secretion [6]. Since uterine functions are under the control of ovarian hormones, it is expected that DOX-induced ovarian toxicity can indirectly affect uterine functions.…”
mentioning
confidence: 99%
“…To circumvent the ovarian toxicity of DOX, which will impair ovarian hormone production thus indirectly affect uterine functions, and to investigate potential long-term impact of DOX on the uterus, young adult ovariectomized CD-1 mice (8 weeks old, Envigo) were given an intraperitoneal injection once with PBS or DOX (10 mg/kg, equivalent to a human chemotherapeutic dose of ∼600 mg/M 2 [6]). Thirty days later, each set of mice was randomly assigned into three groups and subcutaneously injected with oil, 17β-estradiol (E2, 4.5 μg/kg, one dose, dissected 6 h later), or progesterone (P4, 60 mg/kg, three doses at 0, 24, and 48 h, and dissected 6 h after the last injection [9]), respectively, to mimic the changes of ovarian hormones prior to embryo implantation in mice [4].…”
mentioning
confidence: 99%